2019
DOI: 10.1177/1477153519837946
|View full text |Cite
|
Sign up to set email alerts
|

The whiteness of lighting and colour preference, Part 2: A meta-analysis of psychophysical data

Abstract: In this work, the correlation between the perceived whiteness of lighting and the corresponding colour preference of observers was comprehensively investigated based on the data of 19 groups of experiments collected from 14 studies. The dataset included 13 experiments with constant correlated colour temperature and 6 experiments with multiple correlated colour temperatures, with illuminance levels ranging from 200 lx to 500 lx. For the five studies implemented by the authors, the subjective ratings of colour p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
4
13
0
Order By: Relevance
“…In that work, observers were asked to evaluate the colour appearance of multiple objects against white background under different light sources and the authors concluded from their results that "The chromaticity of the white tone which is seen together with the coloured objects contributes to the colour preference assessment about the coloured objects." Furthermore, in our recent work, we further validated that there was strong correlation between the whiteness of lighting and colour preference, not only by psychophysical results from four groups of psychophysical experiments (Huang et al, 2019b) but also by a meta-analysis of visual data from 19 visual experiments (Huang et al, 2019a). As for this work, obviously, the consistency between the whiteness of lighting and colour preference showed in Figure 4 further consolidates the above findings.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In that work, observers were asked to evaluate the colour appearance of multiple objects against white background under different light sources and the authors concluded from their results that "The chromaticity of the white tone which is seen together with the coloured objects contributes to the colour preference assessment about the coloured objects." Furthermore, in our recent work, we further validated that there was strong correlation between the whiteness of lighting and colour preference, not only by psychophysical results from four groups of psychophysical experiments (Huang et al, 2019b) but also by a meta-analysis of visual data from 19 visual experiments (Huang et al, 2019a). As for this work, obviously, the consistency between the whiteness of lighting and colour preference showed in Figure 4 further consolidates the above findings.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we used a Mann-Whitney U test to investigate whether the colour preference between men and women for certain object under certain light source was significantly different (p < 0.05). Surprisingly, for all the 357 lighting scenarios (visual tests with a certain combination of test object and test light source) depicted in our former papers (Huang et al, 2017(Huang et al, , 2018(Huang et al, , 2019a(Huang et al, , 2020a(Huang et al, ,b, 2021bChen et al, 2020b;Liu et al, 2020;Wang et al, 2020), significant sex difference was only observed in the work that related to blue jeans (Liu et al, 2020). In that study, males and females judged the colour appearance of seven pairs of jeans consecutively and their responses were significantly different for all jeans under two specific lighting conditions: male observers provided significantly higher scores than females under two light sources of 5,500 K, with Duv values (the distance from the test chromaticity coordinates to the Planckian locus) of 0.02 and 0.015, respectively.…”
Section: Introductionmentioning
confidence: 67%
“…In this regard, the previous studies also have reported that the CCT alone is not effective on visual comfort. In fact, the desirable design depends on a balance between the color of the interior surfaces and the CCT (Yang and Jeon, 2020[ 32 ]; Sokolova and Fernández-Caballero, 2015[ 25 ]; Huang et al, 2020[ 10 ]). Therefore, it seems that white or warm light is less effective during the day and especially in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…In the past century and a half, many research projects have investigated the effect of lighting on the perception of the environment, contributing to a comprehensive understanding of the mechanism of visual perception. Studies aimed at finding a correlation between the spectral power distribution (SPD) of light and human visual perception, including colour fidelity [1,2], colour naturalness [3,4], colour discrimination [5,6], colour preference [7][8][9], lighting comfort [10,11], and the whiteness of lighting [12,13], have obtained positive results. More than fifty colour quality metrics involving objective and subjective aspects of perception have been proposed, including the Colour Rendering Index (CRI: Ra) developed by Commission Internationale de l'Eclairage (CIE) [1], Colour Quality Scale (CQS: Qa, Qf, Qp, Qg) [2] developed by National Institute of Standards and Technology (NIST), IES-TM-30 metrics (Rf and Rg) [14] developed by American National Standards Institute (ANSI) & Illuminating Engineering Society of North America, Memory Colour Rendering Index (MCRI) [15], Colour Discrimination Index (CDI) [16], and Gamut Volume Index (GVI) [17].…”
Section: Introductionmentioning
confidence: 99%